Răspunsuri

2014-08-30T15:02:32+03:00
A= \frac{3n+4+5m+8}{2n+3+2m+3}

a=4 =>4= \frac{3n+4+5m+8}{2n+3+2m+3} =>  \frac{4}{1}=  \frac{3n+12+5m}{2n+6+2m}

amplifici pe  \frac{4}{1}  cu 2n+6+2m

=>  \frac{8n+24+8m}{2n+6+2m}=  \frac{3n+12+5m}{2n+6+2m} => \\(8n+24+8m)*(2n+6+2m)=(2n+6+2m)*(3n+12+5m)\\=>\\ [tex]16n^{2} +48n+16mn+48n+144+48m+16mn+48m+ 16m^{2}  6n^{2} +24n+10m+9n+72+30m+6mn+24M+ 10m^{2}

Asta e prima parte... o pun imediat pe a 2-a, ai putina rabdare :)

12 4 12
cred ca asta e tot :p
sper ca ai inteles ce scrie
da
mersi
ok, succes